2015
DOI: 10.2152/jmi.62.245
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cyst arising from the infrapatellar fat pad in a child

Abstract: A ganglion cyst is a cystic swelling containing myxoid matrix and lined by a pseudomembrane (1, 2). These cysts sometimes occur in the knee, mainly arising from the synovial membrane of ligaments. The prevalence of intra-articular ganglion cyst of the knee ranges from 0.2% to 1% as determined by magnetic resonance imaging (MRI) and 0.6% as determined by arthroscopy (3). A ganglion cyst arising from the infrapatellar fat pad is very rare ; only a few cases have been reported to date (4, 5) and age in these case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Most of them originated from the anterior or posterior cruciate ligament. In contrast, only three cases originated from the infra-patellar fat pad [20]. Sugiura et al reported a ganglion cyst arising from the infra-patellar fat pad of a 10-year-old boy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most of them originated from the anterior or posterior cruciate ligament. In contrast, only three cases originated from the infra-patellar fat pad [20]. Sugiura et al reported a ganglion cyst arising from the infra-patellar fat pad of a 10-year-old boy [14].…”
Section: Discussionmentioning
confidence: 99%
“…A ganglion cyst in the knee joint often arises from ACL or PCL [ 5 ], but rarely arises from the infrapatellar fat pad. Sugiura et al reported the ganglion cyst arising from the infrapatellar fat pad of 10-year-old boy [ 6 ]. Sloane et al .…”
Section: Discussionmentioning
confidence: 99%
“…Three reports detailed ganglion cysts and pigmented villonodular synovitis, while no studies were identified with a primary focus on fat pad impingement syndrome in this population, with the exception of one case report on a child with HD. 52,[92][93][94] Two limited epidemiological studies on sports injuries in adolescents reported a prevalence of 0.4-4.5% for fat pad injury as a cause of anterior knee pain. 51,54 One study also detailed herniation of the IFP through the patellar retinaculum as a rare cause of an asymptomatic anterior knee mass in children.…”
Section: Epidemiologymentioning
confidence: 99%